Immunomagnetic selection of CD34+peripheral blood stem cells for autografting in patients with breast cancer - Hohaus, Stefan; Pförsich, Margit; Martin, Simona; Abdallah Khalafallah, Alhossain; Lin, Yung Sheng; Funk, Liane; Voso, Maria Teresa; Kaul, Sepp; Schmid, Hans; Wallwiener, Diethelm; Haas, Rainer (British journal of haematology, 1997)
Contamination of transplants with tumour cells may contribute to relapse after peripheral blood stem cell transplantation (PBSCT). We studied the feasibility of CD34+ cell selection from blood-derived autografts obtained following G-CSF-supported cytotoxic chemotherapy in a group of 25 patients with breast cancer (10 with high-risk stage II/III and 15 with stage IV without bone or bone marrow involvement). Using immunomagnetic beads (Isolex 300 SA, Baxter) CD34+ cells were enriched and released by chymopapain resulting in a median purity of 95% (range 82-99%) and a median recovery of 80% (range 27-132%). The enrichment procedure did not change the proportion of CD34+ subsets coexpressing HLA-DR, CD38 and Thy-1, while L-selectin was removed from the cell surface following selection. Using a sensitive immunocytological technique with a cocktail of epithelial-specific antibodies (anti-cytokeratin 8, 18 and 19; HEA125; BM7 and BM8), five leukaphereses products contained epithelial cells, whereas the selected CD34+ cell fraction was free of tumour cells. A neutrophil count of 0.5×109/l and a platelet count of 20×109/l was reached after a median time of 14 and 10 d following 40 high-dose chemotherapy (HDC) cycles. Our results indicate that immunomagnetic selection of CD34+ cells yields highly purified autografts devoid of tumour cells whereas the engraftment ability of the progenitor and stem cells is fully retained.
Elektronische Reproduktion der Druck-Ausgabe 29. Oktober 2003
Gesehen am 13.05.2025